Recidivism to Drugs Abuse - Hussein Jasim, Sabreen; Abdullah, Zainab (Al-Adab Journal, 2021)
The research dealt with the subject of recidivism to drug abuse, and its impact on Iraqi society, especially youth, in a way that leads to a decrease in their productive capacity and an absence of social stability, and many deviations from society’s standards, in addition to the spread of crime, and the reasons for the occurrence of recidivism to abuse differ from one person to another according to the nature of his personality And his social and psychological state, and the first days to stop using drugs are considered one of the most difficult days, and the rate of relapse occurring in them is very high because they are accompanied by painful withdrawal symptoms and the urgent desire to use drugs, and search to explore their mysteries indicating the types of drugs that a person uses, the triggers of recidivism its stages and the most important factors The drive to stick to drug abuse.